Accompaniment in Creating Learning Modul Based on the Merdeka Curriculum for Aswaja Subjects in Formal Education in Sidoarjo - S.A.P., Rangga Sa'adillah; Muslih, Muslih; Shofiyuddin, Ahmad; Apologia, Milla Ahmadia; Ibrahim, Mohd Hairy (Jurnal Soeropati, 2024)
The Merdeka Curriculum provides opportunities for teachers to make adjustment to local school conditions. Aswaja subjects are important to be adjusted based on the demands of curriculum development. This accompaniment aims to assist the preparation of learning modules based on the Merdeka Curriculum in Aswaja subjects in Sidoarjo. This accompaniment uses the ABCD approach and involves 30 participants of Aswaja teachers in Sidoarjo Regency who have succeeded in compiling learning module products for Aswaja subjects at all levels of education ranging all levels of education from elementary school to high school which have never been done. In addition to the product in the form of learning modules, this accompaniment succeeded in encouraging the active involvement of Aswaja subject teachers, exploring the latest learning innovations to attract students' attention to Aswaja subjects, forming local leaders, encouraging the role of stakeholders.